Leadership Style, Compensation And Its Effect On Employee Performance (PT. SSBP Case) - Elly Alfrida; Petrus T. Resi; Sabam Simbolon (Fakultas Bisnis, 2020)
This research is aimed at understanding the relationship of leadership style and compensation on employee performance at PT SSBP considering that the two independent variables are the main factors that determines the success of a company as general as well as PT SSBP. The research obtained data from 144 respondents out of 210 total employees. A questionnaire was prepared to catch their perception on leadership style and compensation and how they affect their performance in the company they work with. From the data obtained and the analysis result shows that the relationship and the contribution of leadership style and compensation on the performance of employees is strong and significant, either partially or simultaneously. Therefore as managerial instruments, leadership style and compensation are extremely important factors to be considered and continuously updated in order to keep and maintain employees motivation that in turn will boost their performance,